Retroperitoneal approach for robot-assisted partial nephrectomy: technique and early outcomes - Porreca,A. (2018)
ABSTRACT Objectives The aim of our study is to present early outcomes of our series of retroperitoneal-RAPN (Robot Assisted Partial Nephrectomy). Materials and methods From September 2010 until December 2015, we performed 81 RAPN procedures (44 at left kidney and 37 at right). Average size was 3cm (1-9). Average PADUA score 7.1 (5-10). Average surgical time (overall and only robot time), ischemia time, blood loss, pathological stage, complications and hospital stay have been recorded. Results All of the cases were completed successfully without any operative complication or surgical conversion. Average surgical time was 177 minutes (75-340). Operative time was 145 minutes (80-300), overall blood loss was 142cc (60-310cc). In 30 cases the pedicle was late clamped with an average ischemia time of 4 minutes (2-7). None of the patient had positive surgical margins at definitive histology (49pT1a, 12pT1b, 3pT2a, 2pT3a). Hospital stay was 3 days (2-7). Conclusions The retroperitoneal robotic partial nephrectomy approach is safe and allows treatment of even quite complex tumors. It also combines the already well known advantages guaranteed by the da Vinci® robotic surgical system, with the advantages of the retroperitoneoscopic approach.